Recommendations for Spot-Spray Treatment of Tropical Soda Apple with Milestone - Jason Ferrell; Brent Sellers (EDIS)
SS-AGR-262, a 2-page fact sheet by Jason Ferrell and Brent Sellers, reports the results of a field experiment to determine the rate and application procedure necessary to maximize TSA control with spot-treatments of Milestone. Published by the UF Department of Agronomy, April 2007.